An Attention-Based Architecture for Context Switch Detection - Tsapatsoulis, Nicolas; Kasderidis, Stathis; Taylor, John G. (My University, 2007)
In the era of Pervasive Computing (Weiser 1991), software applications, hidden in information appliances (Birnbaum 1997), will be continuously running, in an invisible manner (Weiser 1993), aiming at the best fulfilment of human users’ needs. These applications should be characterized by interaction transparency and context-awareness (Abowd 1999). Interaction transparency means that the human users are not aware that there is a computing module embedded in a tool or device that they are using. It contrasts with the actual transparency of current interactions with computers: both traditional input-output devices such as mice and keyboards and manipulations such as launching browsers and entering authentication information (by using a login and a password) are purely computer oriented. Context awareness refers to adaptation of the behaviour of an application depending on its current environment. This environment can be characterized as a physical location, an orientation or a user profile. A context-aware application can sense the environment and interpret the events that occur within it. Sensing the environment is very important for adapting the provided to the user services.
Keywords: Ubiquitous computing; Electronic control